Integration of model-based engineering with system safety analysis. (1st January 2013) - Scholz, Sven; Thramboulidis, Kleanthis
System safety is the property of the system that characterises its ability to prevent from hazards, which may lead to accidents. Traditionally, system developers are not familiar with system safety analysis processes which are performed by safety engineers. One reason is the gap that exists between the traditional development processes, methodologies, notations and tools and the ones used in safety engineering. Semi-formal notations that support a coherent modelling of a system are considered mandatory for safety critical systems. With the evolvement of model-based engineering methods, several approaches have been proposed to integrate the traditional development process with safety engineering. In this paper, an approach to integrate safety engineering with an SysML-based development process is presented. Preliminary hazard analysis is adapted and applied to an SysML-based system requirements specification. A case study from the railway domain illustrates the proposed approach.